2015
DOI: 10.2298/pif1502107s
|View full text |Cite
|
Sign up to set email alerts
|

Chemical control of field dodder in alfalfa

Abstract: SUmmARyParasitic flowering plants have recently come into focus of research interests as a result of their notable expansion and increasing damage that they are causing in agricultural fields. Damage caused by field dodder in alfalfa crops mainly includes reduced yield of fresh biomass and considerable decrease in seed production. Effective control of field dodder in alfalfa crops necessarily includes a number of preventive measures and procedures, as well as chemical control. The effectiveness of glyphosate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…on the woody species Punica granatum L. (Bewick et al, 1988). Sarić-Krsmanović et al (2015) found that glyphosate applied at the rates of 288 and 360 g a.i. ha significantly reduced field dodder in alfalfa crop.…”
Section: Chemical Control Of Field Doddermentioning
confidence: 99%
See 2 more Smart Citations
“…on the woody species Punica granatum L. (Bewick et al, 1988). Sarić-Krsmanović et al (2015) found that glyphosate applied at the rates of 288 and 360 g a.i. ha significantly reduced field dodder in alfalfa crop.…”
Section: Chemical Control Of Field Doddermentioning
confidence: 99%
“…Furthermore, imazethapyr treatment in an infested carrot crop has been found to cause less damage than its application in non-infested crop, which again points at the potentials of exploiting the low translocation rates of non-selective herbicides for selective control of parasite weeds (Nir et al, 1996). However, Sarić-Krsmanović et al (2015) found imazethapyr to have a weak effect on field dodder heavily infesting alfalfa as 78-95% of dodder plants remained after treatment (imazethapyr, 150 g a.i. ha).…”
Section: Chemical Control Of Field Doddermentioning
confidence: 99%
See 1 more Smart Citation
“…and Orobanchaceae family are an obligatory parasite that connects to the petiole or stem of host crops, causing severe losses in production efficiency (Albert et al 2010;Ashigh and Marquez 2010). The yield reduction in crops such as tomato and alfalfa infested with parasitic plants can reach as high as 60% (Mishra 2009;Saric-Krsmanovic et al 2015;Yoder and Scholes 2010). Parasite nematodes, such as Heterodeera glycines, Meloidogyne incognita and Globodera rostochiensis are obligate parasites that use a specialized spear called a stylet and have a unique and specialized way to infect their hosts.…”
Section: Introductionmentioning
confidence: 99%
“…However, glyphosate is only useful (labeled) in glyphosate-resistant varieties of alfalfa, even though it was shown to be effective at low doses (75 to 150 g ae ha −1 ) that nonresistant alfalfa tolerates (Dawson 1989). Diquat and paraquat are also effective in controlling dodder postattachment but are nonselective, resulting in damage to alfalfa (Saric-Krsmanovic et al 2015).…”
mentioning
confidence: 99%